Systematic review of the diagnosis and management of necrotising otitis externa: Highlighting the need for high‐quality research. (22nd February 2023) - Takata, Junko; Hopkins, Michael; Alexander, Victoria; Bannister, Oliver; Dalton, Lucy; Harrison, Laura; Groves, Emily; Kanona, Hala; Jones, Gwennan Llwyd; Mohammed, Hassan; Andersson, Monique I.; Hodgson, Susanne H.
Abstract: Objectives: To present a systematic review and critical analysis of clinical studies for necrotising otitis externa (NOE), with the aim of informing best practice for diagnosis and management. Design: Medline, Embase, Cochrane Library and Web of Science were searched from database inception until 30 April 2021 for all clinical articles on NOE. The review was registered on PROSPERO (ID: CRD42020128957) and conducted in accordance with PRISMA guidelines. Results: Seventy articles, including 2274 patients were included in the final synthesis. Seventy‐three percent were retrospective case series; the remainder were of low methodological quality. Case definitions varied widely. Median patient age was 69.2 years; 68% were male, 84% had diabetes and 10% had no reported immunosuppressive risk factor. Otalgia was almost universal (96%), with granulation (69%) and oedema (76%) the commonest signs reported. Pseudomonas aeruginosa was isolated in 62%, but a range of bacterial and fungal pathogens were reported and 14% grew no organism. Optimal imaging modality for diagnosis or follow‐up was unclear. Median antimicrobial therapy duration was 7.2 weeks, with no definitive evidence for optimal regimens. Twenty‐one percent had surgery with widely variable timing, indication, or procedure. One‐year disease‐specific mortality was 2%; treatment failure and relapse rates were 22% and 7%, respectively. Conclusion: There is a lack of robust, high‐quality data to support best practice for diagnosis and management for this neglected condition. A minimum set of reporting requirements is proposed for future studies. A consensus case definition is urgently needed to facilitate high‐quality research.